Genetic diversity in cowpea (Vigna unguiculata) using isozyme electrophoresis - Reis, C.M.G. (2011)
Cowpea [Vigna unguiculata (L)Walp] is an important crop in many countries of tropical Africa, Asia and South America. In Portugal it is a non-fertilized and a non-irrigated crop normally used as a cover crop for summer fallow ground. Crop vegetation and non-harvested pods are an important protein supplement for sheep grazing, which are in delivery phase at this time.